Let?s speak : (advanced level) (Deepublish, 2016)
This book is a book about English speaking (conversation) learning in advanced level which was arranged practically and concisely, and it is one of books used by English Academy Bengkulu as a primary learning materials. However, this book is intended not only for students of English Academy, but is also intended for all English learners in the world. Each section in this book comes with a wide range of expositions, vocabularies, and topics wich are varied and applicable in everyday life, like fashion, bussines, college life, news reading, reporting an event or incidence and many more.The themes in this book have been adapted to conversations in everyday life, so it can help learners at an advanced level to learn how to deliver English in a good and right way.